The therapeutic ratio is preserved for radiotherapy or cisplatin treatment in BRCA2-mutated prostate cancers - Vesprini, Danny; Narod, Steven A.; Trachtenberg, John; Crook, Juanita; Jalali, Farid; Preiner, John; Sridhar, Srikala; Bristow, Robert G. (Canadian Urological Association Journal, 2013)
Prostate cancers in patients with a mutation in BRCA2 have earlier disease onset and an aggressive course, often necessitating the use of systemic therapy. However, these tumours are DNA repair-defective and could respond favourably to Parp inhibitors or DNA-damaging agents, depending on the therapeutic ratio (ratio of tumour response to normal tissue toxicity). We describe 3 patients treated with precision radiotherapy or cisplatin who responded favourably to both agents, yet did not suffer undue toxicity. We review the concept of treating such patients with agents that are selectively toxic to repair-deficient tumours.